STUDI EKSPERIMENTAL PERFORMANCE KAVITASI WATERJET PROPULSI - Wulfilla M. Rumaherang; J. Louhenapessy; Mesak F. Noya; Cendy S. Tupamahu (ALE Proceeding, 2021)
Cavitation is a complex phenomenon of dynamic processes in hydraulic machines that can cause a decrease in energy performance, vibration and damage the blade surfaces. Analysis of cavitation symptoms in hydraulic machines is carried out through cavitation performance studies, namely the relations between energy parameters. Each hydraulic machine has a critical value on a different cavitation performance curve. Therefore, a study of the effect of cavitation changes is needed to determine the working zone of hydraulic machines without cavitation. In this study, cavitation performance analysis was carried out on a waterjet propulsor model with 5 impeller blades and 7 stator blades using experimental methods. The cavitation coefficient was varied at Ïƒ = 2.25 to 0.25 by setting and controlling the inlet pressure on the cavitation test rig. The critical point value will be observed at the point where the thrust coefficient decreased to 3.28%. The results showed that cavitation begins at Ïƒ = 1, the critical point is obtained at Ïƒ = 0.75. From these studies, we find that waterjet must be operated at conditions where is Ïƒ > 0.75.